Advances in Photodetectors Research and Applications - Chee, Kuan (IntechOpen, 2019)
This book provides a wide-ranging overview of the current state-of-the-art and new trends in photodetector design and research. Written by a team of internationally renowned experts, with contributions from universities, research institutes and industries, this work is suitable for students and professionals interested in studying and dealing with photodetector design and technology, as well as the wide gamut of related applications. Its coverage includes: physics and fundamentals of photodetectors; physical models of photodetector operation; new materials, design, processing and function of photodetectors in related applications; testing, monitoring and calibration; and research progress in photodetector-related areas. Theoretical aspects, design and simulation principles, and important experimental results are thoroughly addressed, embodying a comprehensive account of current activity in this important field of research and industry.